Ecology of freshwater and estuarine wetlands - Batzer, Darold P.; Sharitz, Rebecca R. (University of California Press, 2014)
"This second edition of this important and authoritative survey provides students and researchers with up-to-date and accessible information about the ecology of freshwater and estuarine wetlands. Prominent scholars help students understand both general concepts of different wetland types as well as complex topics related to these dynamic physical environments. Careful syntheses review wetland soils, hydrology, and geomorphology; abiotic constraints for wetland plants and animals; microbial ecology and biogeochemistry; development of wetland plant communities; wetland animal ecology; and carbon dynamics and ecosystem processes. In addition, contributors document wetland regulation, policy, and assessment in the US and provide a clear roadmap for adaptive management and restoration of wetlands. New material also includes an expanded review of the consequences for wetlands in a changing global environment. Ideally suited for wetlands ecology courses, Ecology of Freshwater and Estuarine Wetlands, Second Edition, includes updated content, enhanced images (many in color), and innovative pedagogical elements that guide students and interested readers through the current state of our wetlands"--Provided by publisher